Dissection of coronary artery: A clinical overview. Issue 4 (April 2021) - Modaragamage Dona, Ann Christine; Abuelgasim, Eyad; Abuelgasim, Biyaser; Kermali, Muhammed; Zahra, Syeda Anum; Hewage, Savini; Harky, Amer
Highlights: Coronary artery dissection is a critical and can be lethal condition. Spontaneous coronary artery dissection warrants further arterial investigations. Traumatic coronary artery dissection is uncommon. Intervention should be based on the extent of the disease. Number of vessels involved can be a determining factor for management type. Abstract: Spontaneous coronary artery dissection (SCAD) is a rare but life-threatening disorder. SCAD is gaining importance as an emerging cause of acute coronary syndrome (ACS), especially in otherwise healthy young women. While SCAD and ACS show similarity in presentation, the management of SCAD differs to that of ACS. If not managed properly SCAD can lead to sudden death. This review examines the pathophysiology, clinical presentation, diagnostic algorithms, and the current and future management of SCAD.